ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS TERTULIS SISWA SMP - Annisa Mutia Dien Islamy; Heru Kurniawan; Wharyanti Ika Purwaningsih (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
The purpose of this study was to describe the written mathematical communication skills possessed by junior high school students. The material used is a flat quadrilateral. The subjects in this study were students of class VII E at SMP Negeri 4 Purworejo. Data collection techniques used observation, mathematical communication skills test results, interview results, and documentation study. The analysis technique used is in the form of data reduction, data presentation, and drawing conclusions. Based on the results of research and discussion, junior high school students' written mathematical communication skills on rectangular plane material are classified as high-level mathematical communication skills and have been able to achieve all indicators of mathematical communication skills.